THE ROLE OF THE SCHOOL PRINCIPAL IN IMPROVING TEACHER PERFORMANCE (A CASE STUDY AT SMKN 2 SEKOTONG, WEST LOMBOK REGENCY, WEST NUSA TENGGARA) - Agus Wirahadi Jayakusuma; Kristina Sedyastuti; Dianawati Suryaningtyas (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to examine the quality of education at SMK Negeri 2 Sekotong and to understand how the school principal's leadership contributes to improving teacher performance at the same institution. The research employs a descriptive qualitative approach. The subjects of this study include the school principal, teachers, and administrative staff. Data were gathered through in-depth interviews, observation, and document review, while data analysis was conducted using triangulation techniques. The study was carried out at SMK Negeri 2 Sekotong, located in Sekotong Village, Sekotong District, West Lombok Regency, West Nusa Tenggara Province. The findings reveal that the school principal plays multiple roles in improving teacher performance as a leader, manager, supervisor, and motivator. These roles are realized through professional development initiatives, continuous academic supervision, the creation of a conducive work environment, as well as consistent motivation and personal example. Supporting factors in teacher performance improvement include strong leadership commitment from the principal and a collaborative relationship among school members, while the main obstacles include limited facilities and infrastructure, as well as the burden of administrative tasks placed on teachers. The study concludes that the interviews with the principal and other informants showed a strong degree of consistency. This consistency was further verified through source and technique triangulation, where data from interviews were cross-checked against observational findings and documentation. The research data, therefore, can be considered to have a sound level of credibility, in accordance with triangulation theory.